Professional Challenges Facing Pharmacists Working at Public Hospitals in an Iraqi Province: A Qualitative Study - Zahraa Nassrullah; Ali Azeez Al-Jumaili (College of Pharmacy University of Baghdad, 2023)
In Iraq, because of the dramatic turnovers facing the country for three decades, pharmacists continue to experience significant professional challenges in both the public and private sectors. The present study aimed to explore the professional challenges and obstacles facing Iraqi pharmacists working in public hospitals. This qualitative study included face-to-face semi-structured interviews with open-ended questions with hospital pharmacists. The participants were selected purposefully (with ≥ 3 years of experience) to work at governmental hospitals in Karbala province between December 2022 and April 2023. The audio-recording interviews were scripted. Thematic analyses were used to generate themes and subthemes from the interviews. Thirty-two pharmacists participated in this study. The study found that there are many challenges facing Iraqi pharmacists in hospitals. Some of which are related to the pharmacists themselves, such as suboptimal competency with an overwhelming number of pharmacists in each hospital, while the others are related to suboptimal organizational conditions, such as inadequate interdisciplinary collaboration, an unfriendly hospital environment as patients' confrontation, unequal task distributions, and inadequate technology and tools. According to the study findings, greater emphasis should be placed on improving multidisciplinary teamwork, pharmacist competency, the pharmacists' role in hospitals and securing the supply of essential medicines. Most participants recommend enhancing quality over quantity of pharmacists in addition to finding areas and horizons to benefit from these large numbers of pharmacists. Keywords: Iraqi pharmacists, hospital pharmacists, challenges, obstacles, Qualitative study.